THE INFLUENCE OF BRAND EQUITY ON CONSUMER PURCHASING DECISIONS FOR GREENFIELDS FRESH MILK - Nisa Fitriyani; Nia Rosiana (Universitas Sebelas Maret, 2025)
The development of the dairy industry in Indonesia aligns with the growing demand for milk. Greenfields is a brand that has succeeded in becoming the market leader for fresh milk in Indonesia, but it is not yet able to be in the Top Brand Award. The research aims to identify consumer characteristics and analyze the influence of brand equity on consumer purchasing decisions for Greenfields Fresh Milk. The study was conducted in Jakarta. We used descriptive analysis and structural equation modeling partial least squares (SEM-PLS) to analyze the total research sample of 125 respondents. The results reveal that the majority of the consumers are women aged 18-25, residing in South Jakarta, and possessing a high school education. Most consumers are private employees with incomes from IDR 5,000,001-IDR 7,000,000 and expenditures on consumption from IDR 500,000-IDR 1,000,000 per month, with a frequency of consuming fresh milk 1–5 times per month. SEM-PLS analysis shows that brand equity has a significant positive effect on purchasing decisions. Based on the results, Greenfields can expand its target market to include children and conduct more intensive promotions